Comparison of apical Microleakage using Ni-Ti with stainless steel finger spreaders - Shahi, Shahriar; Shakouie, Sahar; Rahimi, Saeed; Yavari, Hamid Reza; Mohammadi, Narmin; Abdolrahimi, Majid (Iranian Endodontic Journal, 2010)
INTRODUCTION: The purpose of this in vitro study was to compare apical microleakage after obturation with Nickel-Titanium (NiTi) compared to Stainless Steel (SS) finger spreaders. MATERIALS AND METHODS: Eighty straight single-rooted human teeth were instrumented using step-back technique. The specimens were randomly divided into four groups. The two experimental groups (n=30) and the negative control group (n=10) were obturated by lateral condensation technique with Ariadent gutta-percha and AH26 sealer. The roots in the positive control group (n=10) were instrumented but not obturated. In one group, SS and in another group NiTi spreaders were used. Microleakage evaluation was conducted using dye penetration method t-test was used for statistical analysis. RESULTS: The results showed statistically significant differences between NiTi and SS groups (P=0.022), with the greatest dye penetration in SS group and the least in NiTi group. CONCLUSION: According to the results of the present study using NiTi spreader decrease apical microleakage in endodontically treated teeth. [Iranian Endodontic Journal 2009;4(4):149-51]